Characteristics of Herbal Medicine Users and Adverse Events Experienced in South Korea: A Survey Study. (10th April 2017) - Jang, Soobin; Kim, Kyeong Han; Sun, Seung-Ho; Go, Ho-Yeon; Lee, Eun-Kyung; Jang, Bo-Hyoung; Shin, Yong-Cheol; Ko, Seong-Gyu
Abstract : Background. This survey aimed to investigate the characteristics of users and nonusers of herbal medicine and the adverse events experienced due to herbal medicines in South Korea. Methods. The questionnaire consisted of safety, using experience, using type, usage and nonusage reason, purchase location, and adverse events of herbal medicine. The survey was administered by online. Results. Of the total 1, 134 respondents, 726 (64.0%) considered herbal medicine safe, and 693 (61.1%) answered that they have taken herbal medicines within the past year. Most common place to purchase them was "TKM hospital or clinic" (63.6%), and most participants (72.2%) took a decoction from a TKM institution. The biggest reason for taking them was for "health improvement" (57.3%), and the reasons for not using them was "medication not necessary" (63.7%). Among those who took herbal medicines, 46 experienced adverse events, and the most frequently reported symptoms were digestive disorders (52.2%). Of the 46 participants who experienced adverse events, 20 (43.5%) were treated by TKM doctors. Conclusions. This study suggests that regulation of herbal medicines is needed in order to resolve problems related to the safety of herbal medicines.